The Existence of Positive Solutions for Singular Impulse Periodic Boundary Value Problem - Zhaocai Hao; Tanggui Chen (International Journal of Differential Equations)
We obtain new result of the existence of positive solutions of a class of singular impulse periodic boundary value problem via a nonlinear alternative principle of Leray-Schauder. We do not require the monotonicity of functions in paper (Zhang and Wang, 2003). An example is also given to illustrate our result.